2019
DOI: 10.3390/ijerph16183263
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Forest Resting Environments on Stress Using Virtual Reality

Abstract: To explore the effects of different types of forest environments for forest therapy, this study focused on forest resting environments. Seven representative forest resting environments found in field research in Beijing were used as independent variables and were shown to subjects by a virtual reality (VR) video. Stress level was used as the dependent variable, and blood pressure, heart rate, salivary amylase, and the Brief Profile of Mood States (BPOMS) were used as physiological and psychological indicators.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 70 publications
4
150
0
2
Order By: Relevance
“…Control is often used, such as being in an urban environment, where a negative effect on the psychological and physiological well-being of the subjects has been observed [50]. Another way to assess the impact of the forest environment on humans is to simulate the impact of this environment in controlled conditions, for example by reproducing the images and sounds that occur in a forest environment, using a monitor [51], or by using virtual reality [52]. In this case, the control environment can be an image, a sound or virtual reality depicting the urban environment.…”
Section: Virtual Nature Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control is often used, such as being in an urban environment, where a negative effect on the psychological and physiological well-being of the subjects has been observed [50]. Another way to assess the impact of the forest environment on humans is to simulate the impact of this environment in controlled conditions, for example by reproducing the images and sounds that occur in a forest environment, using a monitor [51], or by using virtual reality [52]. In this case, the control environment can be an image, a sound or virtual reality depicting the urban environment.…”
Section: Virtual Nature Environmentsmentioning
confidence: 99%
“…Representing nature in the form of images, and video or virtual reality has been found to have a positive effect on human well-being, mental and physiological health [52][53][54]. Virtual nature (VN) environments reduces stress [55] and have a positive effect on dementia symptoms [56].…”
Section: Virtual Nature Environmentsmentioning
confidence: 99%
“…In most of the mentioned studies, the restorative effect of exposure to natural environments was evaluated by means of psychophysiological measures [42][43][44], whereas, in our study, only self-report questionnaires were employed; on the other hand, any assessment other than online questionnaires was unfeasible due to the lockdown restrictions. However, the SPRAS is composed of items which measure the severity of anxiety symptoms that are likely to be observed in the domain of a physiological individual's response to stress [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, it was suggested that nature experience may promote our capacity to recover from a stressful event by helping to mitigate states of arousal within minutes from the exposure [42]. A restorative effect on stress level was recently observed in two studies aimed at determining the beneficial physiological effects of exposure to a virtual reality video showing forest resting [43], or high biodiversity [44] environments. Similar to previous studies conducted in the framework of the SRT, the restorative effect was evaluated after experimentally inducing stress mental state (using a stressful mental arithmetic task).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most of the research works based on VR simulating the real environment are optimistic about its representation validity. VR is widely used in spatial cognition research, such as on the security of enclosed park spaces and the influence of virtual nature environments on mental actions [15][16][17]. At the same time, due to its high controllability and repeatability, VR can provide an even more in-depth experience than on-site observation.…”
Section: Introductionmentioning
confidence: 99%